Lasing from Mechanically Exfoliated 2D Homologous Ruddlesden–Popper Perovskite Engineered by Inorganic Layer Thickness. Issue 39 (13th August 2019) - Liang, Yin; Shang, Qiuyu; Wei, Qi; Zhao, Liyun; Liu, Zhen; Shi, Jia; Zhong, Yangguang; Chen, Jie; Gao, Yan; Li, Meili; Liu, Xinfeng; Xing, Guichuan; et al.
Abstract: 2D Ruddlesden–Popper perovskites (RPPs) have aroused growing attention in light harvesting and emission applications owing to their high environmental stability. Recently, coherent light emission of RPPs was reported, however mostly from inhomologous thin films that involve cascade intercompositional energy transfer. Lasing and fundamental understanding of intrinsic laser dynamics in homologous RPPs free from intercompositional energy transfer is still inadequate. Herein, the lasing and loss mechanisms of homologous 2D (BA)2 (MA) n −1 Pb n I3 n +1 RPP thin flakes mechanically exfoliated from the bulk crystal are reported. Multicolor lasing is achieved from the large‐ n RPPs ( n ≥ 3) in the spectral range of 620–680 nm but not from small‐ n RPPs ( n ≤ 2) even down to 78 K. With decreasing n, the lasing threshold increases significantly and the characteristic temperature decreases as 49, 25, and 20 K for n = 5, 4, and 3, respectively. The n ‐engineered lasing behaviors are attributed to the stronger Auger recombination and exciton–phonon interaction as a result of the enhanced quantum confinement in the smaller‐ n perovskites. These results not only advance the fundamental understanding of loss mechanisms in both inhomologous and homologous RPP lasers but also provide insights into developing low‐threshold, substrate‐free, and multicolor 2D semiconductor microlasers. Abstract : Lasing and loss dynamics of mechanically exfoliated, homologous 2D Ruddlesden–Popper perovskite (RPP, (C4 H9 NH3 )2 (CH3 NH3 ) n −1 Pb n I3 n +1 ) crystals are reported. The Auger recombination and the electron–phonon coupling are the major loss channels, and they increase with the decreasing of inorganic layer thickness ( n ), leading to larger threshold in smaller‐ n RPPs, and even the absence of lasing action for n < 3 above 78 K.